2015
DOI: 10.1515/nsad-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Khat or Targeting Somalis? A Discourse Analysis of Project Evaluations on Khat Abuse among Somali Immigrants in Scandinavia

Abstract: Background In Denmark, Norway and Sweden, the use of the psychoactive plant khat is widely seen as a social and health problem exclusively affecting the Somali immigrant population. Several projects by governmental and municipal bodies and agencies have been initiated to reduce khat use and abuse within this target population. Aim This article analyses the khat abuse discourse as it is presented in evaluation reports describing projects initiated by the social services to reduce khat abuse. Methods Six pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As khat use has been constructed as a "Somali problem" and made ethnic, solutions have been proposed based on culture and ethnicity in various ways, for example "cultural competence" (Nordgren, 2015). In relation to dominant discourses about khat use in Sweden, it is notable that the interviewees in this study seldom suggested solutions and help based on ethnicity or culture.…”
Section: "It Is Not Only Somalis Who Chew" -The Somalis-khat Associationmentioning
confidence: 91%
See 4 more Smart Citations
“…As khat use has been constructed as a "Somali problem" and made ethnic, solutions have been proposed based on culture and ethnicity in various ways, for example "cultural competence" (Nordgren, 2015). In relation to dominant discourses about khat use in Sweden, it is notable that the interviewees in this study seldom suggested solutions and help based on ethnicity or culture.…”
Section: "It Is Not Only Somalis Who Chew" -The Somalis-khat Associationmentioning
confidence: 91%
“…Khat use has been claimed to cause social problems of various sorts, particularly socioeconomic disadvantages and "integration problems" Carrier, 2007, chapter 7;Nordgren, 2013;Nordgren, 2015;.…”
Section: Khat Use As a Social Problemmentioning
confidence: 99%
See 3 more Smart Citations